Laparoscopic gastrectomies for cancer: The ACOI-IHTSC national guidelines. Issue 5 (September 2012) - Bracale, Umberto; Pignata, Giusto; Lirici, Marco Maria; Hüscher, Cristiano GS; Pugliese, Raffaele; Sgroi, Giovanni; Romano, Giovanni; Spinoglio, Giuseppe; Gualtierotti, Monica; Maglione, Valeria; Azagra, Santiago; Kanehira, Eiji; et al.
Abstract: Guidelines for laparoscopy and cancer of stomach have been outlined by several scientific societies: The main recommendation being that laparoscopy should be used only by surgeons already highly skilled in gastric surgery. The laparoscopic approach to gastric cancer surgery has become more and more frequent in most Italian centers. On behalf of the Guideline Committee of the Italian Society of Hospital Surgeons and the Italian Hi-Tech Surgical Club, a panel of experts analyzed the highest evidence of all scientific papers focusing on laparoscopic gastrectomies for cancer and published from 2003 to 2011, and drew these national guidelines. Laparoscopic gastrectomy may be considered as a safe procedure with better short-term and comparable long-term results. compared to open gastrectomy (Grade A). There is a general agreement that a laparoscopic approach to the treatment of gastric cancer should be chosen only by surgeons already highly skilled in gastric surgery and other advanced laparoscopic interventions. Furthermore, the first procedures should be carried out during a tutoring program. Diagnostic laparoscopy is strongly recommended as the first step of laparoscopic as well as laparotomic gastrectomies (Grade B). Additional randomized controlled trials (RCT) that compare and investigate the long-term oncological outcomes of laparoscopic assisted gastrectomy are required.